Interstitial and Langerhans' dendritic cells in chronic periodontitis and gingivitis - Patricia Ramos Cury; Cristiane Furuse; Ana Elisa Amaro Rodrigues; José Alexandre Barbuto; Cavalcanti de Araújo; Ney Soares de Araújo (Sociedade Brasileira de Pesquisa Odontológica, 2008)
The aim of the present study was to compare quantitatively the distribution of dendritic cell subpopulations in chronic periodontitis and gingivitis. Fourteen biopsies from patients with chronic periodontitis and fifteen from patients with gingivitis were studied. An immunoperoxidase technique was used to quantify the number of Langerhans' cells (CD1a) and interstitial dendritic cells (factor XIIIa) in the oral and sulcular and junctional/pocket epithelia and in the lamina propria. A greater number of factor XIIIa+ dendritic cells in the lamina propria and CD1a+ dendritic cells in the oral epithelium were observed in gingivitis compared to the periodontitis group (p = 0.05). In the sulcular and junctional/pocket epithelia and in the lamina propria, the number of CD1a+ dendritic cells was similar in the gingivitis and periodontitis groups. In conclusion, the number of Langerhans' cells in the oral epithelium and interstitial dendritic cells in the lamina propria is increased in gingivitis compared to periodontitis, which may contribute to the different pattern of host response in these diseases.